Grandir en une nuit : le discret redécoupage des municipalités allemandes - Daniel Florentin (EchoGéo)
The reconfiguration of municipal boundaries in Germany has been a fairly silent process, often neglected by German urban studies. This territorial transformation rests upon a paradoxical situation: although municipal authorities are regulated by a strong municipal law system warranting them a large autonomy, the design of their boundaries is a regional (Land) prerogative. Local boundaries is consequently a regional matter. Over the last fifty years, regional authorities have constantly sought to transform these boundaries and reduce the number of municipalities. These processes of territorial transformation are subject to dissents and conflicts, and do participate to changes in the ways the (German) city can be conceived, which this article will address.